Computational Interrogation of The Human Norovirus-Host Cell Interactions Facilitated by A-Type Antigen - Abdulkadir Kocak; Muslum Yildiz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Norovirus infectivity, which causes norovirus-induced gastroenteritis,depends on the interaction between capsid protein VP1 of the virus and hostcell HGBA receptors that tailor the cell membrane surface. The interactionresults in VP1-HGBA complex formation prior to infection. The details of thisinteraction have been provided by x-ray structures of HGBA-VP1 complexes, butthe dynamic nature of this interaction is not fully uncovered. Therefore, thedynamics that drive the formation of VP1-HGBA complex, which is crucial fordeveloping new therapeutic approaches to find a cure for gastroenteritisdisease, need to be elucidated. Here, we computationally analyzed the wild typeVP1 capsid protein in complex with A-type HGBA antigen to unravel interactionsthat are important for virus to enter inside the host cell during infection. Wehave found that the ligand binding causes a fluctuation in a distant loop whichresides in the interface of capsid building blocks, VP proteins. Thisfluctuation leads an instability in capsid particle that may be an indicationfor virus uncoating mechanism during the cell penetration.